Elaboration of the bischofite eye drops using the biopharmaceutical criteria - B. B. Sysuev; Ye. B. Sysuev; I. Yu. Mitrofanova (Бюллетень сибирской медицины)
Our research is of theoretical and practical importance and aims at the development of ophthalmological dosage form comprising mineral component (bischofite). It is mineral complex consisting of 96% magnesium chloride with macro- and microelements. Having carried out complex physicochemical and biopharmaceutical researches in vitro, we developed composition and technology of 10% bischofite solution in the form of eye drops. After is one of the perspective tools in technological researches. After using of the analytic hierarchy process by T. Saaty the optimal eye drops composition was selected according to all chosen criteria for this pharmaceutical form.